2016
DOI: 10.1051/0004-6361/201628516
|View full text |Cite
|
Sign up to set email alerts
|

A model for distortions of polarisation-angle curves in radio pulsars

Abstract: Context. Some radio pulsar profiles (in particular those of millisecond pulsars) contain wide emission structures which cover large intervals of pulse phase. Local distortions of an average curve of polarisation angle (PA) can be identified in such profiles, and they are often found to be associated with absorption features or narrow emission components. Aims. The features may be interpreted as a convolution of a lateral profile of an emitter with a microscopic radiation pattern of a non-negligible angular ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…2, until recently the procedure followed for calibrating pulsar observations with the NRT was limited. With seemingly correct pulsar timing results with the NRT (as e.g., determined in the context of multi-telescope pulsar timing studies), and a relative paucity of pulsar polarization studies with this telescope (see for instance Theureau et al 2011;Dyks et al 2016;Desvignes et al 2022, for examples of NRT pulsar polarization measurements), the validity of the former polarimetric calibration procedure had not been studied in detail prior to this work. However, detailed comparisons of NRT polarization profiles with reference results obtained at other telescopes, and significant modifications in the observed polarization properties of pulsars concurrent with instrumental changes in 2019, prompted us to revisit the procedure for calibrating pulsar observations with the NRT, and the procedure for extracting TOAs from NRT data.…”
Section: Introductionmentioning
confidence: 99%
“…2, until recently the procedure followed for calibrating pulsar observations with the NRT was limited. With seemingly correct pulsar timing results with the NRT (as e.g., determined in the context of multi-telescope pulsar timing studies), and a relative paucity of pulsar polarization studies with this telescope (see for instance Theureau et al 2011;Dyks et al 2016;Desvignes et al 2022, for examples of NRT pulsar polarization measurements), the validity of the former polarimetric calibration procedure had not been studied in detail prior to this work. However, detailed comparisons of NRT polarization profiles with reference results obtained at other telescopes, and significant modifications in the observed polarization properties of pulsars concurrent with instrumental changes in 2019, prompted us to revisit the procedure for calibrating pulsar observations with the NRT, and the procedure for extracting TOAs from NRT data.…”
Section: Introductionmentioning
confidence: 99%
“…The debate between the "corecone" beam models and other models (such as the "patchy" beam, fan-beam, microbeam pattern et al) as well as multi-frequency observed data have been persisted by many authors (e.g. Lyne & Manchester 1988;Kramer et al 1994;Manchester 1995;Gil & Krawczyk 1996;Melrose 1999;Mitra & Deshpande 1999;Gangadhara et al 2001;Han & Manchester 2001;Kijak & Gil 2002;Manchester et al 2005;Karastergiou & Johnston 2007;Maciesiak et al 2012;Beskin & Philippov 2012;Fonseca et al 2014;Wang et al 2014;Cerutti et al 2016;Dyks et al 2016;Pierbattista et al 2016;Teixeira et al 2016). Besides, some theoretical perspectives (such as: the radio radiation beam is a hollow beam without a core cone; the pulse profiles at lower frequency are wider than those at higher frequencies) have been challenged by a large number of observations.…”
Section: Introductionmentioning
confidence: 99%